Thermodynamic Studies on Adsorption of Methylene Blue and Congo Red Dyes Using Groundnut Shell and Sorghum Husk Biosorbents - Hammari, Abubakar M.; Hammanadama, Faruk A.; Gadc, Ajuji I. (Mikailalsys Journal of Advanced Engineering International, 2025)
The effects of temperature on the adsorption of Methylene Blue (MB) and Congo Red (CR) dyes using groundnut shell (GS) and sorghum husk (SH) biosorbents were investigated. Adsorption capacities were determined through spectrophotometric analysis, and thermodynamic parameters including Gibbs free energy (ΔG), enthalpy (ΔH), and entropy (ΔS) were calculated. The study found that MB adsorption onto SH was spontaneous and endothermic, while other conditions exhibited non-spontaneous and exothermic behavior. These findings demonstrate the potential of GS and SH as viable, low-cost biosorbents for dye removal in wastewater treatment, highlighting their practical application in sustainable environmental remediation.